THE INTERNAL SURFACE OF WALLS AND THE FORMATION OF INTRA-AXILLARY STRAIGHT SINUS DURA MATER OF THE HUMAN BRAIN - Черно, В.С. (World of Medicine and Biology, 2013)
The article contains data results of micro-macroscopic studies lyumenalnoyi surface and the formations of intra-axillary straight sinus dura mater of the human brain. It was found that intra-axillary straight sinus formation have a number of morphological features, based on its placement and transport function leading to outflow of blood from the brain.